Transactions on edutainment VII - Pan, Zhigeng (Lecture Notes in Computer Science, 2012)
This journal subline serves as a forum for stimulating and disseminating innovative research ideas, theories, emerging technologies, empirical investigations, state-of-the-art methods, and tools in all different genres of edutainment, such as game-based learning and serious games, interactive storytelling, virtual learning environments, VR-based education, and related fields. It covers aspects from educational and game theories, human-computer interaction, computer graphics, artificial intelligence, and systems design. The 27 papers of this volume deal with virtual human; graphics rendering and 3D animation; games and 2D animation; and digital media and its applications.